3D type I collagen environment leads up to a reassessment of the classification of human macrophage polarizations. (July 2019) - Court, Magali; Malier, Marie; Millet, Arnaud
Abstract: Macrophages have multiple roles in development, tissue homeostasis and repair and present a high degree of phenotypic plasticity embodied in the concept of polarization. One goal of macrophage biology field is to characterize these polarizations at the molecular level. To achieve this task, it is necessary to integrate how physical environment signals are interpreted by macrophages under immune stimulation. In this work, we study how a 3D scaffold obtained from polymerized fibrillar rat type I collagen modulates the polarizations of human macrophages and reveal that some traditionally used markers should be reassessed. We demonstrate that integrin β2 is a regulator of STAT1 phosphorylation in response to IFNγ/LPS as well as responsible for the inhibition of ALOX15 expression in response to IL-4/IL-13 in 3D. Meanwhile, we also find that the CCL19/CCL20 ratio is reverted in 3D under IFNγ/LPS stimulation. 3D also induces the priming of the NLRP3 inflammasome resulting in an increased IL-1β and IL-6 secretion. These results give the molecular basis for assessing collagen induced immunomodulation of human macrophages in various physiological and pathological contexts such as cancer.